Correlation Analysis of Economic Growth with social conflict in Jambi Province 2010 - 2022 - -, Yuliana (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study aimed to analyze economic growth’s correlation with social conflicts in Jambi Province between 2010 and 2022 using quantitative descriptive analysis. Secondary and primary data were analyzed using Pearson Product Moment Correlation with SPSS 25. The analysis showed that the correlation between GRDP and social conflict in Jambi Province is 0.869 and the two variables have a perfect positive linear correlation. Kerinci district has a high, perfect, positive, linear correlation of 0.912. Merangin district indicated -0.028, implying no correlation and that the two variables are opposite. Furthermore, the Sarolangun district showed 0.352, indicating a weak but positive linear correlation. Batang Hari district showed 0.652, implying a high unidirectional correlation. Muaro Jambi district indicated 0.919, or a very high, positive, and perfect linear correlation. Tanjung Jabung Timur district showed 0.540, meaning the two variables have a moderate, positive, and perfect linear correlation. Tanjung Jabung Barat district obtained 0.827, meaning the two variables have a very high and positive perfect linear correlation. Tebo district showed 0.801, implying a high and positive perfect linear correlation between the two variables. Furthermore, Bungo district indicated 0.473, meaning the two variables have a moderate and positive perfect linear relationship. Jambi City achieved 0.658, implying a high and positive perfect linear correlation. Sungai Penuh City indicated 0.612, meaning the two variables have a high and perfect positive linear correlation. A positive correlation means that conflict intensity increases with GRDP.